Neuroendocrine cells associated with neuroendocrine carcinoma of the breast: nature and significance. Issue 8 (3rd May 2012) - Kawasaki, Tomonori; Mochizuki, Kunio; Yamauchi, Hideko; Inoue, Shingo; Kondo, Tetsuo; Oishi, Naoki; Nakazawa, Tadao; Yamane, Tetsu; Koshimizu, Yoshihito; Tsunoda, Hiroko; Yagata, Hiroshi; Inoue, Masayuki; et al.
Abstract : Background: The developmental mechanisms of breast neuroendocrine carcinoma (B-NEC) have not been sufficiently analysed and are not well understood. Aims: To investigate NE cells in the background tissues surrounding B-NECs. Methods: Three cases (four breasts) having many NE cells in the background tissues of multifocal B-NECs were identified at the University of Yamanashi Hospital and St Luke's International Hospital, Japan. These patients were, respectively, 28-, 31- and 38-year-old women with no familial history of NE tumour. The totally-resected breasts were serially studied by immunohistochemistry for specific NE markers (chromogranin A/synaptophysin) and the morphologies and/or localisation of NE cells were investigated. Results: Immunohistochemical examination showed extensively-distributed NE cells in the background mammary ducts/lobules of the NECs in all breasts. These NE cells were classifiable into three emerging patterns: isolated/scattered, clustered and circumferential. Their distributions were intermingled and were not clearly related to B-NEC foci. NE cells were morphologically polygonal, oval or columnar with sometimes eosinophilic and/or fine-granular cytoplasm and round-to-ovoid nuclei lacking atypia. Some cells were located between epithelial and myoepithelial cells. Apical snouts were occasionally observed in NE cells forming luminal structures. Conclusions: Benign-appearing NE cells in the parenchyma of a breast with NEC could be regarded as hyperplastic from their emerging patterns and distribution; this NE cell hyperplasia may be associated with the histogenesis of B-NEC as a precancerous condition. These observations might raise questions about the treatment for B-NEC.